Current best practice in the evaluation and management of malignant pleural effusions - Steven Walker; Anna C. Bibby; Nick A. Maskell (Therapeutic Advances in Respiratory Disease, 2017)
Malignant pleural effusions (MPEs) are an important cause of cancer-related mortality and morbidity. It is a heterogeneous group of conditions, which leads to debilitating symptoms and confers a poor prognosis. Recent well-designed randomized trials have provided a broader evidence base for an expanding range of treatment options. Together, with new prognostic scoring systems and a greater understanding of how different patient phenotypes respond to treatment, this allows greater personalization of management. This article will discuss the current evidence on evaluation and management of MPEs.